Understanding Teachers’ Perceptions and Challenges in Fostering Scientific Attitudes in Elementary Science Education - Ari Widodo; Ernawulan Syaodih; Muslim; Fransiska Astri Kusumastuti (Jurnal Elementaria Edukasia, 2026)
Scientific attitude is an important component of science learning as it shapes how students think, evaluate evidence, and respond to phenomena. However, in elementary classrooms, its development often receives less attention than knowledge and skills. This study aims to explore teachers’ perceptions and practices in constructing students’ scientific attitudes in elementary science learning. A descriptive survey design is used involving 59 elementary school teachers from several cities in Java, Indonesia. Data are collected through an online questionnaire consisting of closed and open-ended questions, and analyzed using descriptive statistics and thematic identification. The results show that most teachers have a general understanding of scientific attitude, but it remains limited and is mainly associated with curiosity. Teaching practices are dominated by questioning and discussion, while the use of inquiry-based activities is still low. In addition, teachers tend to assess scientific attitude based on students’ activeness rather than using structured indicators. Teachers also report challenges related to students’ low engagement and limited instructional time. This study concludes that there is a gap between teachers’ understanding and their classroom practices in developing scientific attitude, indicating the need for more structured instructional and assessment approaches in elementary science learning.